1980
DOI: 10.1002/app.1980.070250614
|View full text |Cite
|
Sign up to set email alerts
|

The influence of thermal history on internal stress distributions in sheets of PMMA and polycarbonate

Abstract: The through‐thickness birefringent patterns (nx – nz) of PMMA and polycarbonate (PC) are measured as a function of thickness, cooling rate, and annealing time. A method is demonstrated for separating the elastic stress from the residual birefringence. The residual birefringence is explained as the residual orientation induced when cooling through the galss transition. The shape of the elastic (tempering) stress distribution is apparently independent of the cooling rate and annealing time, the choice of polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…On the other hand, PET/PC blends were opaque, apparently because of the phase separation between PET and PC, as shown in Figure 1. These results clearly demonstrate that FBP/PC alloy system is absolutely compatible and miscible, whereas conversely, PET/PC alloys are completely immiscible and incompatible 14–15…”
Section: Resultsmentioning
confidence: 66%
“…On the other hand, PET/PC blends were opaque, apparently because of the phase separation between PET and PC, as shown in Figure 1. These results clearly demonstrate that FBP/PC alloy system is absolutely compatible and miscible, whereas conversely, PET/PC alloys are completely immiscible and incompatible 14–15…”
Section: Resultsmentioning
confidence: 66%
“…Although most ofthe studies are of a preliminary nature, the phenomenon itself has been defined and distinguished from other phenomena that frequently accompany residual stresses, such as molecular orientation. In recent studies, the level and distribution of R. S. in thermally treated amorphous polymers (1)(2)(3) as well as in melt-processed (4-7) and cold-rolled (8)(9) polymers, have been investigated. The effect of thermal history, including quenching through a variety of temperature gradients and levels with respect to the polymer glass discussed in Part I of the presint study (10).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on polymer materials by many researchers showed that after the annealing of polymer materials there is still certain amount of birefringence remained [7,8] .…”
Section: Transverse Birefringence Due To Molecular Alignmentmentioning
confidence: 98%
“…This quenching-induced birefringence can be removed by annealing process [5,7] , in which the temperature of the fibre is raised to a certain level, and then the fibre is cooled down to room temperature gradually and slowly with very similar temperature across the whole cross section of the fibre. This will relax the internal thermal stress due to the quenching temperature gradient and therefore remove the birefringence caused by quenching effect.…”
Section: Transverse Birefringence Due To the Quenching Effectmentioning
confidence: 99%